Design of novel HIV-1 protease inhibitors incorporating isophthalamide-derived P2-P3 ligands: Synthesis, biological evaluation and X-ray structural studies of inhibitor-HIV-1 protease complex. Issue 19 (1st October 2017) - Ghosh, Arun K.; Brindisi, Margherita; Nyalapatla, Prasanth R.; Takayama, Jun; Ella-Menye, Jean-Rene; Yashchuk, Sofiya; Agniswamy, Johnson; Wang, Yuan-Fang; Aoki, Manabu; Amano, Masayuki; Weber, Irene T.; Mitsuya, Hiroaki
Graphical abstract: Abstract: Based upon molecular insights from the X-ray structures of inhibitor-bound HIV-1 protease complexes, we have designed a series of isophthalamide-derived inhibitors incorporating substituted pyrrolidines, piperidines and thiazolidines as P2-P3 ligands for specific interactions in the S2-S3 extended site. Compound 4b has shown an enzyme Ki of 0.025 nM and antiviral IC50 of 69 nM. An X-ray crystal structure of inhibitor 4b -HIV-1 protease complex was determined at 1.33 Å resolution. We have also determined X-ray structure of 3b -bound HIV-1 protease at 1.27 Å resolution. These structures revealed important molecular insight into the inhibitor–HIV-1 protease interactions in the active site.